2017
DOI: 10.1071/rdv29n1ab157
|View full text |Cite
|
Sign up to set email alerts
|

157 Effect of FSH Starvation (Coasting) Following Superovulation on Oocyte Competence and Cloning Efficiency in Goats

Abstract: Oocyte competence plays a key role in the overall efficiency of reproductive biotechnologies. In cattle, FSH starvation following superovulation (coasting) improves oocyte competence, blastocyst yield and pregnancy outcome when used in ovum pickup-in vitro production programs. The aim of this study was to compare the effect of coasting after exogenous FSH stimulation on goat oocyte quality and competence to support in vitro maturation and in vivo embryo development following cloning procedures in goats. Donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Next, the pellet was resuspended and cultivated in DMEM/F12 (Gibco) medium supplemented with 10% fetal bovine serum (FBS; Gibco), 1% penicillin–streptomycin (Gibco) and 10 ng/mL epidermal growth factor (EGF; Sigma) and incubated at 37.5°C and 5% CO 2 . Fibroblasts were isolated from an ear biopsy [ 27 ] of non-transgenic or human lactoferrin (hLF) transgenic goats [ 28 ]. Each biopsy was cut into approximately 5 mm pieces and left to rest in six well plates containing DMEM medium (Gibco) supplemented with 10% FBS (Gibco) and 1% penicillin–streptomycin (Gibco) under incubation at 38.5°C and 5% CO 2 until it was possible to see the presence of explant cells in contact with the plate.…”
Section: Methodsmentioning
confidence: 99%
“…Next, the pellet was resuspended and cultivated in DMEM/F12 (Gibco) medium supplemented with 10% fetal bovine serum (FBS; Gibco), 1% penicillin–streptomycin (Gibco) and 10 ng/mL epidermal growth factor (EGF; Sigma) and incubated at 37.5°C and 5% CO 2 . Fibroblasts were isolated from an ear biopsy [ 27 ] of non-transgenic or human lactoferrin (hLF) transgenic goats [ 28 ]. Each biopsy was cut into approximately 5 mm pieces and left to rest in six well plates containing DMEM medium (Gibco) supplemented with 10% FBS (Gibco) and 1% penicillin–streptomycin (Gibco) under incubation at 38.5°C and 5% CO 2 until it was possible to see the presence of explant cells in contact with the plate.…”
Section: Methodsmentioning
confidence: 99%
“…Nivet et al (57) demonstrated that the optimal period between FSH surge and transvaginal aspiration is 54±7 h and well-defined competence window is crucial to obtain optimal oocyte quality in ovarian stimulated milking cows. The coasting strategy following superovulation improves oocyte competence, blastocyst yield and pregnancy outcome when used in ovum pickup-in vitro production programs (58); therefore, it is a useful tool to improve oocyte competence through the contribution in the increase of the potential pool of oocytes to be selected.…”
Section: Coasting To Induce Competence In Large Mammalsmentioning
confidence: 99%